Strategies for enhancing faculty brand through personal branding: Insights from lecturers - Ellyn Eka Wahyu; Yekie Senja Oktora (Jurnal Penelitian, 2023)
Professional branding is a new step in the professional development of a lecturer, which presupposes a holistic process of forming a lecturer's personal brand, which consists of creating a personality image of a lecturer that is attractive, socially recognized, and can be recognized in his professional field. This study aims to identify the extent of the faculty branding process carried out by lecturers of the Business Administration Department of the State Polytechnic of Malang through Instagram social media. A total of 10 respondents were determined using purposive sampling. The data collection method is done by in-depth interview, while the data analysis method uses data triangulation. The results showed that the majority of respondents have carried out professional branding by uploading various outputs that show their respective expertise ranging from education, training (mastery class) to community service. However, there are still no significant findings regarding lecturers' output related to intellectual property rights so that it becomes an opening for further research. Through the results of this study, it can be stated that the Malang State Polytechnic Business Administration Study Program has made efforts to carry out massive faculty branding through lecturer posts on social media.